Implementasi Fuzzy Tsukamoto Dalam Menentukan Harga Gabah Pada Petani - Josua Fernando Simanjuntak; Agnes Prawita Sari; Aulia Nada Syahputri (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2020)
In human life, many things require decision making, including in agriculture. One of them is rice farmers who make the decision to determine the selling price of their grain according to the quality of their grain. By using Fuzzy logic, the grain price can be determined by going through the following stages: Fuzzification, Knowledge Base Formation, Fuzzy Inference, and Defuzzification. One of the Fuzzy logic methods that can be used is the Tsukamoto method, where this method has an output in the form of firm values. To be able to determine the price of grain, the data is taken from the Central Statistics Agency website, so that later prices and levels of grain quality can be determined properly. With this research, the farmers can determine the price of their grain exactly according to the quality of the grain. So that the problem of determining their grain prices can be overcome properly.